Comparative Chemical Composition of the Essential Oils from Pseudognaphalium Robustum, P. Heterotrichium and P. Cheiranthifolium - Urzua-Moll, A; Santander-Meyer, R; Echeverria-Morgado, J (2011)
Sin Editorial Disponible